The Effectiveness of the Think Silently Strategy on Academic Achievement and Science Process Skills among First-Grade Intermediate Students in Biology - Ali Jabbar Yaseen ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This study aims to measure the effectiveness of the Think Silently” strategy on academic achievement and scientific processes among first-grade intermediate students in Biology. The experimental method was employed, using a partially controlled experimental design with two equivalent groups (experimental and control). A total of 62 students participated in the study after excluding those who had previously failed. The experimental group studied the subject using the "Think-Pair-Share" strategy, while the control group was taught using traditional methods. Research tools included an achievement test and a scientific processes test, both of which were validated and verified for reliability statistically. The results revealed a statistically significant difference at the (0.05) significance level between the mean scores of the two groups in favor of the experimental group in both academic achievement and scientific processes levels, with large effect sizes for both variables. This superiority is attributed to the fact that the "Think-Pair-Share" strategy is based on active learning, enhances effective student participation, develops higher-order thinking skills, and strengthens self-directed and systematic knowledge construction. The researcher recommends employing this strategy in science teaching due to its positive impact on improving academic performance and developing scientific processes.DOI: https://doi.org/10.54633/2333-025-058-020